Disfemia dalam Kolom Komentar Akun Youtube Najwa Shihab - Indri Nur Farida; I Ketut Darma Laksana; I Gusti Ngurah Ketut Putrayasa (Udayana University, 2022)
This article examines the use of dysphemia in the comments column of Najwa Shihab's youtube account